Peningkatan Softskil Kompetensi IOT Untuk Siswa-Siswi SMK Muhammadiyah 1 Kramat - Huda, Miftakhul; Sabanise, Yerry Febrian; Sulasmoro, Arfan Haqiqi (LPPM IST AKPRIND Yogyakarta, 2022)
The need for an IOT approach with the world of education, especially at thevocational level so that students can know the development of technological advances.Because in the world of school or college a lot of time is spent on time-consuming activitiesand eventually deviates from the main purpose of educational institutions, for examplechecking student attendance which must be done several times a day. The existence of IoTwill help this inefficient system. Students' knowledge of IoT needs to be increased, studentsfeel the need to increase the provision of material, so the solution is to increase students'knowledge in mastering IoT and IoT components ranging from sensors, CPUs, embeddeddevice operating systems, networking. After carrying out Community Service activities withthe theme IOT Competency Softskill Improvement for Students of SMK Muhammadiyah 1Kramat after participating in this activity, students know IOT better and gain mastery of IOTcomponents.